The influence of pain exacerbation on rear foot eversion and plantar pressure symmetry in women with patellofemoral pain: a cross sectional study - Ali Yalfani; Fatemeh Ahadi; Mohamadreza Ahmadi (BMC Musculoskeletal Disorders)
Abstract Background The patellofemoral joint (PFJ) stress as a primary mechanical stimulus in the patellofemoral pain (PFP) etiology is affected by plantar pressure symmetry. This study evaluated how pain exacerbation affects rear foot eversion and plantar pressure distribution symmetry. Method Sixty women with PFP participated in this study. Pain intensity, rear foot eversion, and plantar pressure were evaluated in the two conditions with and without pain exacerbation during double-leg squats. The MANOVA test was used to compare pain intensity, rear foot eversion, and plantar pressure symmetry between the two conditions. The Pearson correlation was used to evaluate the relationship between the pain intensity with the rear foot eversion and the plantar pressure symmetry. Results The comparison between the two conditions showed a significant difference in pain intensity (P < 0.001, η2 = 0.623), rear foot eversion (P < 0.001, η2 = 0.485), plantar pressure distribution symmetry of the right-left foot (P < 0.001, η2 = 0.438), forefoot and rear-foot of the right foot (P < 0.001, η2 = 0.607), and forefoot and rear-foot of the left foot (P < 0.001, η2 = 0.548). An excellent correlation was observed between the pain intensity with rear foot eversion (P < 0.001, r = 0.835) and plantar pressure distribution symmetry of the right-left foot (P < 0.001, r = 0.812), forefoot and rear-foot of the right foot (P < 0.001, r = 0.834), and forefoot and rear-foot of the left foot (P < 0.001, r = 0.811). Conclusions After the pain exacerbation, the rear foot eversion was greater, and plantar pressure asymmetrical was observed, which can help in the development of PFP severity.